GEOCHEMISTRY OF METASOMATISED SPINEL PERIDOTITE XENOLITHS FROM THE DARIGANGA PLATEAU, SOUTH-EASTERN MONGOLIA - Kononova V.A.; Pervov V.A.; Kurat G.; Brandstätter F.; Embey-Isztin A.; Koeberl C. (My University, 2002)
One fresh (green), one altered (black) and one composite (green/black) peridotite xenolith from the Neogene-Quaternary basalts of the Dariganga Plateau, SE Mongolia, were studied by electron microprobe, X-ray fluorescence, wet chemical and instrumental neutron activation analysis. The history of the upper mantle underneath the Dariganga Plateau has been complex and is characterised by elemental depletions and enrichments processes. The rocks investigated appear to have been processed in several steps, have been moderately depleted (relative to the primitive upper mantle composition) in incompatible elements and subsequently metasomatically enriched in alkalis, Fe, Ca, LREE, Th and U. As a result, most peridotites are moderately depleted in Si, Cr, Ti, HREE and Hf, are slightly enriched in LREE and have elevated Th and U abundances. The minerals in all rocks are out of chemical equilibrium. In the green peridotites disequilibrium is modest but it is severe in the blackened lherzolites. The latter have experienced strong Fe metasomatism accompanied by strong oxidation. As a result, Mg-rich olivines formed by oxidation and precipitation of Fe oxides in the primary olivines (blackening) and Fe-rich olivines formed in the Fe metasomatic event. The latter could only have taken place after the oxidising event, otherwise the Fe-rich olivines would also have been affected by it. Three of the four rocks show negative anomalies (relative to the Ce abundance) of Hf and Ti, one is enriched in these elements, which is considered an indication of the action of carbonatitic melts/fluids in the upper mantle. Enrichment of U over Th in some of our samples seems also to indicate the presence of water in the fluid phase, however, the lack of (OH)-bearing minerals in the Dariganga xenoliths suggests a low activity of water in these fluids. The latest of the metasomatic events probably took place shortly before entrapment of the rocks by the basaltic lava that carried them to the earth’s surface. The composite sample consisting of a green harzburgite and a black lherzolite suggests that blackening took place at the original location of the rock rather than in the basaltic tuff because the latter should have altered the whole xenolith. It also demonstrates that metasomatic processes in the upper mantle can be confined to rather restricted locations with sharp boundaries towards the wall rocks. Blackening as well as the metasomatic events apparently took place because of a better permeability in one part of the rock as compared to the other, probably the result of tectonisation.